PENGUATAN KARAKTER NASIONALISME KH. HASYIM SY’ARI DALAM PEMBELAJARAN PAI DI SMA TRENSAINS TEBUIRENG - Siti Munawaroh; Asriana Kibtiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the decline in the sense of nationalism students due to the rapid development of technology. The aim of this study is to provide an overview of the loss of nationalism in millennials due to the rapid flow of globalization. This research is a qualitative study with a fundamentalist approach. It focuses on understanding the erosion of nationalism among young people. Data collection was carried out through direct observation in the research field and conducting several interviews with several sources from SMA Trensains Tebuireng. The data analysis technique used Domain analysis, which encompasses love of the homeland and the spirit of maintaining unity. The process involved data reduction, data presentation, and drawing conclusions. Finally, data validity was checked. This research was conducted through credibility testing (extending observation, increasing persistence, triangulation). The results of the study indicate that Islamic Religious Education (PAI) learning at SMA Trensains Tebuireng is implemented effectively. There is general Islamic Religious Education (PAI) learning, and there is additional content, namely Aswaja material. The methods used in learning vary. The instillation of KH. Hasyim Asy'ari's Nationalist Values ​​in Islamic Religious Education (PAI) Learning at SMA Trensains Tebuireng includes; a sense of love for the homeland, fostering a spirit of unity.